Percepção dos usuários do sistema de trânsito sobre os diferentes modelos de focos semafóricos existentes em cidades do estado de São Paulo - Costa, Eduardo Fleury (Universidade Federal de São Carlos, 2022)
According to the Brazilian Traffic Code (CTB), signaling is defined as the set of traffic signals and safety methods installed on public roads, to guarantee adequate use, in addition to enabling easy transit for locomotion and transportation, and increase safety for vehicles and pedestrians. Given the great diversity of types of traffic lights that exist, knowing the preference and behavior of road system users who use them daily is of paramount importance. With this, the present work seeks to compare the types of existing light signals and analyze the opinion regarding traffic lights with a countdown and luminous counters in cities in the state of São Paulo. For this, a bibliographic review was carried out, directing all the components of the application of the form with a theoretical basis, being defined parameters and research structures. With the first stage completed, the second stage consisted of the elaboration of an online form, using the Google Forms tool, containing questions that allowed to know about the perception and preference of users about the different types of traffic lights in São Carlos city and its region. From the data obtained, there is a greater tendency in the choice and preference of the research participants for traffic lights with real-time counting. However, it is still too early to say that it is seen as a replacement for the same traditional models, they divide the opinion of several users from users.
Perception of traffic system users on the different models of traffic lights existing in cities in the state of São Paulo
Keywords: Focos semafóricos; Semáforos inteligentes; Semáforos com contadores de tempo; Percepção dos usuários; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES